Abschlussarbeiten an Nordrhein-Westfälischen Designschulen 1990. (Hagen : Karl Ernst Osthaus-Museum, 1990)
Kruse, Andreas ; Sonntag, Karola ; Specker, Heidi ; Stork, Martina ; Kuntze, Dagmar ; Bellmann, Anette ; Plum, Georg ; Nitsch, Manfred ; Preller, Heiko ; Weinand, Andreas ; Reifig, Sabine ; etc.
Abschlussarbeiten an Nordrhein-Westfälischen Designschulen 1990, Karl Ernst Osthaus-Museum, Hagen, 17.11. - 25.11.1990
boek